HARMONY IN HOUSEHOLD: NAVIGATING FAMILY PLANNING IN MODERN CONTEXTS - Khan, Muhammad Ali (Top Journal of Public Policy and Administration (TJPPA), 2024)
Family planning plays a pivotal role in establishing a harmonious equilibrium between the number of family members and the economic capacity of households. Employing modern scientific knowledge, wise parents can effectively manage and control the size of their families, thereby addressing the challenge of high birth rates. This revolutionary practice holds the promise of reducing birth rates to a manageable level, contributing to the overall well-being of families and societies. Beyond demographic considerations, family planning emerges as a critical tool in safeguarding the lives and health of women and children. By preventing untimely and unwanted pregnancies, it serves as a protective shield, reducing women’s exposure to the inherent health risks associated with childbirth and abortion. This, in turn, empowers women, who often shoulder the primary caregiving responsibilities, by granting them more time to attend to the needs of their children and prioritize their own well-being. While the concept of family planning may seem contemporary, its roots delve deep into history. Even in the early days of Islam, the practice of withdrawal during intercourse was noted among the Sahaba Ikraam (RU). Despite the awareness of this practice, the Holy Prophet Muhammad (SAW) did not forbid it, showcasing a nuanced understanding of family planning within the Islamic tradition. This paper explores the multifaceted dimensions of family planning, emphasizing its role in demographic management, maternal and child health, and its historical relevance in Islamic traditions. By examining the intersection of modern scientific knowledge and cultural contexts, we aim to provide insights into the evolving landscape of family planning practices and policies.